A study on the online resources cited in the theses and special problems done at the University of the Philippines School of Library and Information Studies - Honrade, Lorraine Dawn G. (2008)
The Internet is a unique medium in which information is published. With the increase of its popularity as information source is a concern about the preservation of its content. It is in this light that the study is focused on the online resources cited in the theses and special problems done at the University of the Philippines-Diliman School of Library and Information Studies. Four hundred ninety-seven theses and special problems were studied.